Improving Children’s Speaking Skills Through the “Can Phone” Game Using Family Photos at Bunga Bangsa Early Childhood Education Center - Purniati Purniati; Ranny Fitria Imran; Asnawati Asnawati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the low speaking ability of children at PAUD Bunga Bangsa, as indicated by their lack of confidence in speaking, limited fluency in conveying messages, and difficulty expressing simple ideas. The study aimed to improve children’s speaking ability through the implementation of a tin-can telephone game supported by family photo media. This study employed classroom action research conducted in two cycles, with each cycle consisting of two meetings. The research subjects were young children enrolled at PAUD Bunga Bangsa. Data were collected through observation, documentation, and field notes. An observation sheet was used as the research instrument to assess the development of the children’s speaking ability. The data were analyzed using qualitative and quantitative descriptive methods. The findings showed a consistent improvement in the children’s speaking ability across each cycle. In Cycle I, the first meeting achieved a percentage of 42.21%, categorized as Beginning to Develop, which increased to 55.55% in the second meeting within the same category. In Cycle II, the percentage increased to 67.79% in the first meeting, categorized as Developing as Expected, and rose significantly to 81.10% in the second meeting, categorized as Developing Very Well. Based on these findings, it can be concluded that the implementation of the tin-can telephone game supported by family photo media was effective in improving the speaking ability of young children. Enjoyable and interactive learning activities enhanced the children’s confidence, fluency, and ability to express simple ideas.